PENEGAKAN HUKUM BAGI KAPAL PENANGKAP IKAN ILEGAL DI PERAIRAN PANTAI PANGANDARAN PROVINSI JAWA BARAT - Riky Pribadi; Herry Farhan Syafiq (Journal Presumption of Law, 2022)
Indonesia is a maritime country in Southeast Asia that has a total area of ​​5,180,083 km2 which includes land and sea. Among these areas, 2/3 of Indonesia's area is an ocean, and 1/3 of its territory island. Indonesia's land area is 1,922,570 km2 which spans an area of ​​3,977 miles. Meanwhile, Indonesia's ocean area is 3,257,483 km2. The sea area compared to the land area makes Indonesia's main strength in the fisheries sector. Indonesia's geographical condition in the form of an archipelago and directly adjacent to a number of countries results in many threats and challenges. Therefore, Indonesia is called a maritime country. The breadth of Indonesia's marine area makes the majority of the income of the residents of coastal communities or near the sea lip work as fishermen. The benefits of the sea are unavoidable for coastal communities, thus this maritime must be maintained for the sake of security, benefit, and prosperity and the welfare of coastal communities will be maintained, both downstream and upstream or in government. The purpose of this research is to enforce the law forcing it like what happened, especially in the coastal area of ​​Pengandaran where there is physical evidence of the shipwrecked illegal fishing vessel. Thus, what is the problem in this research is related to illegal fishing or fishing without a permit with stages and a descriptive-analytic juridical approach based on positive laws and regulations and other rules related to illegal fishing, exclusive economic zones (EEZ), The law of the sea, the crime of illegal fishing.